1994
DOI: 10.1111/j.1423-0410.1994.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

MAR, a Novel High‐Incidence Rh Antigen Revealing the Existence of an Allelic Sub‐System Including Cw (Rh8) and Cx (Rh9) with Exceptional Distribution in the Finnish Population

Abstract: We present new genetic evidence obtained from population studies on Finns and from the studies on Finnish blood donors as well as their selected families using an antibody that defines a novel high-incidence Rh antigen MAR. Anti-MAR antibody shows an antithetical relationship to both anti-Cw and anti-Cx. The Rh antigens Cw (RH8) and, more strikingly, Cx (RH9) have each an exceptionally high frequency in Finns. Our studies on their genetic relationship indicate that the three antigens Cw, Cx and MAR behave as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Additional testing was performed on samples from the case reported in 1983, and the results are included here. The specificity of the antibody made by our patient, CJ, is slightly different from that of the antibodies previously reported, which were made by two MAR– persons 1,2 . Evidence is provided to indicate that examples of “anti‐MAR” differ slightly, depending upon the C W /C X status of the antibody maker.…”
contrasting
confidence: 81%
See 3 more Smart Citations
“…Additional testing was performed on samples from the case reported in 1983, and the results are included here. The specificity of the antibody made by our patient, CJ, is slightly different from that of the antibodies previously reported, which were made by two MAR– persons 1,2 . Evidence is provided to indicate that examples of “anti‐MAR” differ slightly, depending upon the C W /C X status of the antibody maker.…”
contrasting
confidence: 81%
“…We report here the first example of an antibody, directed at a high‐incidence Rh antigen, made by a patient with DC W e/DC W e MAR‐negative RBCs. The specificity of the antibody appears to be related to anti‐MAR (anti‐RH51), which was produced by a patient with the rare DC W e/DC X e phenotype 1 . An antibody with similar specificity was made by a DC X e/DC X e female patient and reported in an abstract in 1983 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only individuals who are combined heterozygous for RhC w and C x (RhC w C x ) or homozygous for RhC w or RhC x , or who are Rh null or RhD-, are MAR-(like)-negative. The original MAR-negative individual (RhC w C x ) was found in Finland [13]. Our studies revealed that in our donor population in Southwestern Germany only one of 19,000 blood donors is MAR-negative.…”
Section: Discussionmentioning
confidence: 87%